Cyclic ethylene phosphates with (CH2)nCOOR and CH2CONMe2 substituents: synthesis and mechanistic insights of diverse reactivity in aryloxy-Mg complex-catalyzed (co)polymerization. Issue 47 (24th November 2021) - Nifant'ev, Ilya E.; Shlyakhtin, Andrey V.; Bagrov, Vladimir V.; Tavtorkin, Alexander N.; Ilyin, Sergey O.; Gavrilov, Dmitry E.; Ivchenko, Pavel V.
Abstract : Herein we present a comparative study of the reactivity of ethylene phosphates with –O(CH2 ) n COOMe ( n = 1–3, 5), –CH2 COO t Bu, –OCHMeCOOMe, and –OCH2 CONMe2 substituents in BHT-Mg catalyzed ROP. Abstract : A novel pathway is proposed for the formation of branched poly(ethylene phosphate)s during the coordination ring-opening polymerization (ROP) of ethylene phosphates catalyzed by a 2, 6-di- tert -butyl-4-methylphenoxy (BHT) magnesium complex, [(BHT)Mg(μ-OBn)(THF)]2 (Mg1 ). Electron-donating fragments in the substituents at the P atom of the ethylene phosphates and the stability of chelate Mg complexes were hypothesized to drive the formation of ethylene phosphate macromonomers. This hypothesis was validated through a comparative experimental and theoretical study of the ROP reactivity of the ethylene phosphates with –O(CH2 ) n COOMe ( n = 1–3, 5), –CH2 COO t Bu, –OCHMeCOOMe, and –OCH2 CONMe2 substituents (1–7 ). In good agreement with the results of theoretical modeling, glycolate- and lactate-substituted ethylene phosphates 1, 5, and 6 formed highly branched polymers, and the participation of the BHT-Mg glycolate intermediate in ROP was confirmed by the presence of –P(O)(OCH2 COOMe)2 fragments in the homopolymer of 1 . Notably, the reaction of amide-substituted 7 with Mg1 quantitatively afforded benzyl ethylene phosphate without subsequent ROP. The copolymerization of 1 with ethyl ethylene phosphonate furnished branched polymers, the architectures of which were determined by spectral and rheological studies. Consequently, new –OCH2 COX substituted cyclic phosphates can be used as efficient branching (X = OR) or chain termination (X = NR2 ) agents.